Chemometric study on the electrochemical incineration of diethylenetriaminepentaacetic acid using boron-doped diamond anode. (May 2018) - Xian, Jiahui; Liu, Min; Chen, Wei; Zhang, Chunyong; Fu, Degang
Abstract: The electrochemical incineration of diethylenetriaminepentaacetic acid (DTPA) with boron-doped diamond (BDD) anode had been initially performed under galvanostatic conditions. The main and interaction effects of four operating parameters (flow rate, applied current density, sulfate concentration and initial DTPA concentration) on mineralization performance were investigated. Under similar experimental conditions, Doehlert matrix (DM) and central composite rotatable design (CCRD) were used as statistical multivariate methods in the optimization of the anodic oxidation processes. A comparison between DM model and CCRD model revealed that the former was more accurate, possibly due to its higher operating level numbers employed (7 levels for two variables). Despite this, these two models resulted in quite similar optimum operating conditions. The maximum TOC removal percentages at 180 min were 76.2% and 73.8% for case of DM and CCRD, respectively. In addition, with the aid of quantum chemistry calculation and LC/MS analysis, a plausible degradation sequence of DTPA on BDD anode was also proposed. Highlights: Boron-doped diamond was initially used to degrade DTPA. DM and CCRD were employed for optimization and comparison purposes. DM model was more accurate than CCRD model in process optimizations. Quantum chemistry calculation and LC/MS were used for mechanistic study. DTPA degradation pathway was proposed.